A recycling method for producing porous water treatment filler using sludge and red mud
By using sludge and red mud to prepare porous water treatment fillers, the problems of high compactness and insufficient water permeability of existing fillers are solved, and more efficient wastewater treatment and better mechanical properties are achieved.
Patent Information
- Application Number
- CN202411826520.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2044-12-12
AI Technical Summary
The existing red mud composite filler has high density and limited water permeability, resulting in low sewage treatment efficiency and mechanical performance needs to be improved.
The base material is prepared by raw materials such as sludge and red mud, and porous water treatment fillers are prepared by ball milling, standing aging, and sintering. The organic matter in the red mud, silt and other components are used to generate gas to form a dense and interconnected pore structure.
The contact effect between filler and sewage is improved, the sewage treatment efficiency is enhanced, and the mechanical properties of filler are improved, avoiding damage to filler during use.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of environmentally friendly material preparation and water treatment, and more specifically, to a recycling method for producing porous water treatment fillers using sludge and red mud. Background Art
[0002] Red mud (Red Mud, Bauxite Residue) is a polluting and insoluble waste residue discharged during the extraction of alumina from bauxite in the aluminum industry. It is a major solid waste discharged in the non-ferrous metallurgical industry. Red mud is reddish in color due to the high content of iron oxide, which is also the origin of its name. In recent years, as the annual output of metallurgical alumina in my country has increased year by year, the annual discharge of red mud has also increased rapidly. Silt (silty soil) refers to a kind of structural soil with fine particles that is deposited in clean water or slow-flowing water environment and formed under the action of physical, chemical or biochemical factors. It belongs to the raw material of silicate and has the following physical and chemical properties: (1) high water content, generally 40-70%; (2) fine particles; (3) mineral composition and chemical composition are similar to clay, and the main oxides are silicon dioxide, aluminum oxide, iron oxide, and a small amount of calcium oxide, magnesium oxide, sodium oxide, potassium oxide, etc.; (4) contains a certain amount of organic matter. According to the country's goal of reducing, harmlessly treating and utilizing industrial waste, choosing a reasonable resource recovery approach is the future development trend for treating and disposing of solid wastes such as sludge and red mud.
[0003] In the related art, there is a red mud composite filler, which is prepared according to the following method: (1) red mud, tourmaline powder, carbon material powder, binder, water and clay mineral are mixed, and then pressed to obtain a matrix blank; (2) the matrix blank is fired, and then naturally cooled to obtain a filler blank; (3) the filler blank is placed in a mixed solution of polyethyleneimine, Tris-HCl and cyclodextrin, soaked, and then dried to obtain the red mud composite filler.
[0004] Regarding the above-mentioned related technologies, the inventors believe that although the red mud composite filler in the related technology realizes the recycling of solid waste, the filler has a certain density and limited water permeability, resulting in relatively poor contact between the filler and sewage, limiting the sewage treatment efficiency. At the same time, the mechanical properties of the filler also need to be improved. Summary of the invention
[0005] In the related art, the contact effect between the filler and the sewage is relatively poor, which limits the sewage treatment efficiency, and the mechanical properties of the filler also need to be improved. In order to improve this defect, the present application provides a recycling method for producing porous water treatment fillers using sludge and red mud.
[0006] The present application provides a method for recycling sludge and red mud to produce porous water treatment fillers, using the following technical solutions:
[0007] A recycling method for producing porous water treatment filler using sludge and red mud comprises the following steps:
[0008] (1) The base material is prepared according to the following weight ratio: 25-35% of clay material, 0.3-2% of binder, 20-30% of red mud, 2-10% of tourmaline powder, 4-8% of foaming agent, 6-10% of medical stone powder, 3-5% of carbonaceous combustion aid, and the balance is supplemented to 100% by inorganic auxiliary materials; the tourmaline powder is ferromagnesian tourmaline, the raw material components of the clay material include silt, and the components of the inorganic auxiliary materials include quartz sand and borax;
[0009] (2) ball milling the prepared base material, adding water and stirring, and then standing and aging under closed conditions to obtain an aged material; adding the aged material into a mold for pressing and forming to obtain a green body, and standing and setting aside for use;
[0010] (3) The green body is preheated and then sintered at 1250-1350°C. After cooling, the sintered product is cut and polished to obtain a porous water treatment filler.
[0011] By adopting the above technical scheme, the present application optimizes the raw material formula, and selects red mud, silt, tourmaline powder, medical stone powder and other components to form the base material. During the sintering process, the organic matter in the silt, the carbonate in the red mud, and the foaming agent and the carbonaceous combustion aid can generate gas and generate pores in situ. In addition, the pore structure of medical stone will also become part of the pore structure of the filler, and at the same time, it is accompanied by the generation of various high-viscosity liquid phases. In this process, the iron oxide in red mud and tourmaline (mainly distributed in their respective mineral phases in the form of hematite) can synergistically promote gas generation, increase the expansion pressure inside the blank, and facilitate the formation of pores. Under the synergistic effect of the high-viscosity liquid phase, gas and mineral primary pores, a dense and interconnected pore structure can be formed inside the blank. Red mud also has good thermal expansion properties, and the quartz in medical stone and the quartz in quartz sand will be transformed into tridymite during the sintering process, and this transformation will also produce volume expansion. The synergistic expansion of red mud, medical stone and quartz sand can effectively counteract the shrinkage pressure generated by the green body during the sintering process, which is conducive to the development and interconnection of pores. In addition to organic matter, sludge also contains mineral phases with fluxing effects such as sodium oxide, potassium oxide, and magnesium oxide. Alkali metal minerals such as sodalite in red mud and borax in inorganic auxiliary materials also have a certain fluxing effect. These fluxing components can synergistically promote the formation of liquid phase, enhance the barrier effect of liquid phase on gas, help to avoid the rapid loss of gas, and also reduce the shrinkage pressure of the green body, which is conducive to fully realizing pore formation. Tridymite has interlaced spearhead twins, is a hard skeleton component, and is not easily soluble in the liquid phase formed under high temperature conditions. Tourmaline will produce mullite and aluminum borate during calcination. Mullite, aluminum borate, and tridymite can form the skeleton structure of the filler together with some minerals in red mud and clay materials, improving the mechanical properties of the filler. In summary, the filler prepared according to the method of the present application not only realizes the recycling of solid wastes such as silt and red mud, but also has an ideal pore structure, can fully contact with sewage, has a good adsorption effect on pollutants, and can complete bacterial biofilm in a relatively short time, which helps to improve the treatment efficiency of sewage. At the same time, it also has good mechanical properties and is not easy to be damaged during use, thereby fully overcoming the defects in the relevant technology.
[0012] Preferably, the inorganic auxiliary material also includes magnesium chloride.
[0013] By adopting the above technical solution, magnesium chloride can react with sodium-containing alkali metal minerals in red mud to convert insoluble sodium into soluble sodium. These soluble sodiums are also fluxing components, and can diffuse with water during static aging, so that the fluxing components are more evenly distributed in the aging material, thereby reducing the shrinkage force of the green body, optimizing the pore structure of the filler, improving the contact effect between the filler and the sewage, and helping to improve the treatment efficiency of sewage.
[0014] Preferably, the inorganic auxiliary material component also includes at least one of magnesium oxide and dolomite.
[0015] By adopting the above technical solution, magnesium is an oxygen-philic element, and magnesium oxide can combine with oxygen during the sintering process to form Mg 2 O or Mg 2 O 2 High-valent oxide intermediates such as magnesium oxide accelerate the transfer of oxygen and can also serve as active centers to weaken the stability of carbon-carbon bonds and carbon-hydrogen bonds in organic matter, thereby promoting the combustion of combustible components. Dolomite can be decomposed into magnesium oxide and carbon dioxide during the sintering process, which helps to increase the total gas production during the sintering process. Both of these magnesium-containing inorganic auxiliary materials can increase the expansion pressure inside the green body by promoting gas production, and the fluxing effect of magnesium oxide can reduce the shrinkage pressure of the green body. The increase in expansion pressure and the reduction in shrinkage pressure jointly improve the pore-forming effect, thereby obtaining a filler with a more developed pore structure, improving the contact effect between the filler and sewage, and helping to improve the filler's treatment efficiency for sewage.
[0016] Preferably, the foaming agent also includes silicon carbide powder.
[0017] By adopting the above technical solution, the present application preferably uses silicon carbide powder as a component of the foaming agent. When silicon carbide is oxidized, it produces carbon dioxide and silicon dioxide, wherein the carbon dioxide escapes in the form of gas, and the silicon dioxide forms a film layer covering the remaining silicon carbide surface, which usually hinders the further oxidation of silicon carbide. The magnesium oxide of the present application and the alkaline components such as soluble sodium dissolved in the red mud can destroy the silicon dioxide film on the surface of silicon carbide, causing silicon carbide to react continuously, overcoming the obstruction of the silicon dioxide film to the oxidation of silicon carbide, thereby fully realizing the foaming of silicon carbide.
[0018] Preferably, the foaming agent also includes silicon carbide fibers.
[0019] By adopting the above technical scheme, silicon carbide fiber has a similar foaming effect as silicon carbide powder, but the difference from silicon carbide powder is that silicon carbide fiber has a one-dimensional structure. After oxidation, it can form interconnected pores on the basis of the one-dimensional structure. The synergistic effect of the one-dimensional structure and the interconnected pores promotes the transfer of gas inside the filler, thereby optimizing the pore-forming effect and helping to improve the filler's efficiency in treating sewage.
[0020] Preferably, in step (2) of the method, before static aging, manganese dioxide sol is added to the base material, and the manganese dioxide sol is prepared according to the following method:
[0021] A potassium permanganate solution is prepared, and fumaric acid is added to the potassium permanganate solution under stirring conditions, and stirring is continued. After standing, a manganese dioxide sol is obtained.
[0022] By adopting the above technical scheme, the present application adopts potassium permanganate as a manganese source, and fumaric acid as a reducing agent to prepare a manganese dioxide sol, and preferably uses the manganese dioxide sol as an additive added to the base material. In the form of a sol, manganese dioxide can be distributed more evenly in the base material. Manganese dioxide can release oxygen during the sintering process, and can also be used as an oxygen supply agent in the oxidation process of silicon carbide, which helps to fully realize the oxidation of silicon carbide, and realizes synergistic pore formation with components such as foaming agents, sludge, red mud, and carbonaceous combustion aids, which helps to improve the treatment efficiency of the filler for sewage.
[0023] Preferably, in the method for preparing the manganese dioxide sol, hexadecyltrimethylammonium bromide is added to the potassium permanganate solution before starting stirring.
[0024] By adopting the above technical scheme, the present application preferably uses hexadecyl trimethyl ammonium bromide as an additive in the process of preparing manganese dioxide sol. Hexadecyl trimethyl ammonium bromide is a cationic surfactant. After being dispersed in an aqueous solution, it will ionize positively charged micelles, and will electrostatically attract negatively charged permanganate ions, thereby improving the dispersion effect of permanganate ions. Therefore, the manganese dioxide sol prepared after adding hexadecyl trimethyl ammonium bromide has better uniformity, and the manganese dioxide particles therein have a smaller particle size, which can better achieve the oxygen supply effect, promote the formation and connection of pores, and help improve the treatment efficiency of fillers for sewage.
[0025] Preferably, in step (2) of the method, after the green body is obtained, an aqueous hydrogen peroxide solution is sprayed onto the surface of the green body.
[0026] By adopting the above technical solution, the present application makes full use of the property of manganese dioxide that can catalyze the decomposition of hydrogen peroxide to produce oxygen, and performs pre-pore treatment at the green body stage. The oxygen produced by the decomposition of hydrogen peroxide can produce a part of the pore structure inside the green body before sintering, improve the effect of gas migration inside the green body generated during the sintering process, make the connectivity between the pores better, and improve the efficiency of the filler in treating sewage.
[0027] Preferably, the clay material further comprises kaolin.
[0028] By adopting the above technical solution, kaolin and magnesium oxide mineral phases are sintered to produce cordierite phase, and the cordierite phase can cooperate with the mullite phase produced after calcining tourmaline to strengthen the skeleton structure in the filler. The formation of the cordierite phase can make the filler have a developed pore structure while also having high mechanical strength, and is not easy to be damaged during use, thereby fully overcoming the defects in the relevant technology.
[0029] Preferably, in step (2) of the method, brown corundum powder is added to the base material before ball milling.
[0030] By adopting the above technical solution, the present application preferably uses brown corundum powder as an additive for the base material. Brown corundum powder can promote the formation of cordierite and has little effect on the pore structure, so that the filler can form a developed pore structure while also having high mechanical strength, and is not easily damaged during use, thus overcoming the defects in the related technology.
[0031] In summary, this application has the following beneficial effects:
[0032] 1. The present application optimizes the raw material formula, and selects red mud, silt, tourmaline powder, medical stone powder and other components to form the base material. The filler prepared according to the method of the present application not only realizes the recycling of solid wastes such as silt and red mud, but also has an ideal pore structure, which can fully contact with sewage, and helps to improve the treatment efficiency of sewage. At the same time, the present application also uses mullite, aluminum borate, tridymite and some minerals in red mud and clay materials to form the skeleton structure of the filler, which improves the mechanical properties of the filler, making it less likely to be damaged during use, and overcoming the defects in the relevant technology.
[0033] 2. The iron oxide in the red mud and tourmaline of the present application can synergistically promote gas generation, increase the expansion pressure inside the green body, and facilitate the formation of pores. Under the synergistic effect of the high-viscosity liquid phase, gas, and the original pores of the raw material components, a dense and interconnected pore structure can be formed inside the green body.
[0034] 3. The present application makes full use of the good thermal expansion properties of red mud and the volume expansion characteristics generated during the transformation of quartz into tridymite. The synergistic expansion of red mud, medical stone and quartz sand is used to counteract the shrinkage pressure generated by the green body during the sintering process, providing sufficient space for the generation and connection of pores, which is conducive to the interconnection between pores.
[0035] 4. The present application utilizes the mineral phases with fluxing effect such as sodium oxide, potassium oxide, magnesium oxide in the sludge, as well as the alkali metal minerals such as sodalite in the red mud and borax in the inorganic auxiliary materials to synergistically achieve the fluxing effect, promote the formation of the liquid phase, enhance the barrier effect of the liquid phase on the gas, help avoid the rapid loss of gas, and also reduce the shrinkage pressure of the green body, which is conducive to fully realizing pore formation.
[0036] 5. The present application releases soluble sodium in red mud with the help of magnesium chloride. The soluble sodium can diffuse along with water during static aging, so that the fluxing components are more evenly distributed in the aging material, thereby reducing the shrinkage force of the green body and optimizing the pore structure of the filler.
[0037] 6. The present application uses at least one of magnesium oxide and dolomite as an inorganic auxiliary material, which not only promotes pore formation but also reduces the shrinkage pressure of the green body by utilizing the fluxing effect of magnesium oxide. The pore formation effect is improved by increasing the expansion pressure and reducing the shrinkage pressure, and a filler with a more developed pore structure can be obtained. DETAILED DESCRIPTION
[0038] The present application is further described in detail below in conjunction with embodiments, preparation examples and comparative examples. The raw materials involved in the present application can all be obtained commercially.
[0039] The following is an explanation using Preparation Example 1.
[0040] Preparation Example 1
[0041] In this preparation example, manganese dioxide sol was prepared according to the following method:
[0042] Potassium permanganate and fumaric acid were weighed in a molar ratio of 3:1, and a potassium permanganate solution with a concentration of 0.375 mol / L was prepared using potassium permanganate. Then, all the fumaric acid was added to the potassium permanganate solution under magnetic stirring conditions, and stirring was continued for 24 hours. After standing for 3 days, a manganese dioxide sol was obtained.
[0043] Preparation Example 2
[0044] The difference between this preparation example and preparation example 1 is that in the method for preparing manganese dioxide sol, hexadecyltrimethylammonium bromide is added to the potassium permanganate solution before starting stirring, and the weight ratio of hexadecyltrimethylammonium bromide to potassium permanganate is 5:1.
[0045] Examples 1-5
[0046] The following description is given by taking Example 1 as an example.
[0047] Example 1
[0048] In this embodiment, the clay material is river sludge, which is dehydrated in advance and crushed to an average particle size of 0.27 mm. The main components of the river sludge are expressed in mass fraction as follows: 2.08% magnesium oxide, 1.27% sodium oxide, 2.24% potassium oxide, 5.58% iron oxide, 16.43% aluminum oxide, 65.87% silicon dioxide, 5.58% loss on ignition, and the rest are impurities; the binder is polyvinyl alcohol (PVA2488); the red mud is sintered red mud with an average particle size of 0.15 mm, and the main oxide components are expressed in mass fraction as follows: 25.42% silicon dioxide, 18.17% aluminum oxide, 13.24% iron oxide, 26.82% calcium oxide, 4.26% titanium dioxide, 9.01% sodium oxide, 2.23% magnesium oxide, and the rest are impurities; the tourmaline powder is ferromagnesian tourmaline with an average particle size of 0.1 mm. The main components are expressed in mass fraction as follows: 52.48% silicon dioxide, 24.66% aluminum oxide, 10.84% boron oxide, 5.44% iron oxide, 3.06% magnesium oxide, and the balance is calcium oxide, titanium dioxide, sodium oxide and potassium oxide; the foaming agent is a carbonate foaming agent with an average diameter of 0.15 mm, and the carbonate foaming agent is a mixture of calcium carbonate and sodium percarbonate in a weight ratio of 1:1; the average particle size of medical stone powder is 0.35 mm, and the main components are expressed in mass fraction as follows: 68.42% silicon dioxide, 18.33% aluminum oxide, 2.56% potassium oxide, 2.01% sodium oxide, 1.98% calcium oxide, and the balance is impurities; the carbonaceous combustion aid is a mixture of poplar wood powder, coke, anthracite and activated carbon in a weight ratio of 4:1:1:2; the components of the inorganic auxiliary materials are a mixture of borax and quartz sand with a fineness modulus of 2.2 in a weight ratio of 1:5;
[0049] This embodiment provides a method for recycling sludge and red mud to produce porous water treatment filler, comprising the following steps:
[0050] (1) The base material is prepared according to the following weight ratio: 35% clay material, 0.3% binder, 30% red mud, 2% tourmaline powder, 8% foaming agent, 10% medical stone powder, 3% carbonaceous combustion aid, and the balance is supplemented to 100% by inorganic auxiliary materials;
[0051] (2) ball milling the prepared base material, adding water and stirring at a solid-liquid ratio of 8:1, and then standing and aging for 48 hours under closed conditions to obtain an aged material; adding the aged material into a mold for pressing and molding to obtain a green body, and standing and setting for use;
[0052] (3) Starting from 105 °C, the temperature was increased to 300 °C at a rate of 1.5 °C / min, and the green body was preheated at 300 °C for 3 h. Then, the temperature was increased to 1250 °C at a rate of 2 °C / min, and sintered at 1250 °C (referred to as the sintering temperature in Table 1) for 12 h. After the sintering, the sintered product was allowed to cool naturally, and then the sintered product was cut and polished to obtain a porous water treatment filler.
[0053] As shown in Table 1, the differences between Examples 1-5 mainly lie in the different raw material ratios of the base material and the sintering temperatures.
[0054] Table 1 Raw material ratio of base material (by mass fraction) and sintering temperature
[0055]
[0056] Embodiment 6-9
[0057] Example 6
[0058] The difference between this embodiment and embodiment 3 is that the inorganic auxiliary material is formed by mixing borax, quartz sand and magnesium auxiliary material in a weight ratio of 1:3:2, the average particle size of the magnesium auxiliary material is 0.17 mm, and the magnesium auxiliary material is magnesium chloride.
[0059] Example 7
[0060] The difference between this embodiment and embodiment 6 is that the magnesium auxiliary material is a mixture of magnesium chloride and magnesium oxide in a weight ratio of 1:2.
[0061] Example 8
[0062] The difference between this embodiment and embodiment 7 is that the magnesium auxiliary material is a mixture of magnesium chloride and dolomite in a weight ratio of 1:2.
[0063] Example 9
[0064] The difference between this embodiment and embodiment 8 is that the magnesium auxiliary material is a mixture of magnesium chloride, magnesium oxide and dolomite in a weight ratio of 1:1:1.
[0065] Embodiment 10-11
[0066] Example 10
[0067] The difference between this embodiment and embodiment 9 is that the foaming agent is a mixture of a carbonic acid foaming agent and a silicon carbide foaming agent in a weight ratio of 1:2, and the silicon carbide foaming agent is silicon carbide powder with an average diameter of 0.2 mm.
[0068] Embodiment 11
[0069] The difference between this embodiment and embodiment 10 is that the silicon carbide foaming agent is formed by mixing silicon carbide powder and silicon carbide fibers in a weight ratio of 5:3, and the average diameter of the silicon carbide fibers is 35 μm and the average length is 2.8 mm.
[0070] Examples 12-14
[0071] Example 12
[0072] The difference between this embodiment and embodiment 11 is that in step (2), before static aging, manganese dioxide sol is added to the base material, and the manganese dioxide sol is prepared according to the method of preparation example 1, and the total weight of manganese dioxide in the manganese dioxide sol is 0.3% of the total weight of the base material.
[0073] Embodiment 13
[0074] The difference between this example and Example 12 is that the manganese dioxide sol is prepared according to the method of Preparation Example 2.
[0075] Embodiment 14
[0076] The difference between this embodiment and embodiment 13 is that in step (2), after the green body is obtained, a hydrogen peroxide aqueous solution is sprayed onto the surface of the green body, the concentration of the hydrogen peroxide aqueous solution is 10%, and the amount of the hydrogen peroxide aqueous solution used is 8% of the weight of the green body.
[0077] Embodiment 15
[0078] The difference between this embodiment and embodiment 14 is that the clay material further comprises kaolin, and the amount of kaolin accounts for 30% of the total weight of the clay material.
[0079] Example 16
[0080] The difference between this embodiment and embodiment 15 is that in step (2), brown corundum powder is added to the base material before ball milling, and the amount of brown corundum powder is 5% of the total weight of the base material.
[0081] Comparative Example 1
[0082] This comparative example provides a red mud composite filler, which is prepared according to the following method:
[0083] (1) 35 kg of red mud, 10 kg of tourmaline powder, 15 kg of carbon material powder, 2 kg of binder, 50 kg of water and 1 kg of clay mineral were mixed and then pressed to obtain a matrix blank;
[0084] (2) sintering the matrix blank at 800°C and cooling it naturally after 4 hours to obtain a filler blank;
[0085] (3) The filler blank was immersed in a mixture of polyethyleneimine solution (polyethyleneimine concentration 20 wt%), Tris-HCl buffer and cyclodextrin in a weight ratio of 60:14:10 for 12 h, and then dried to obtain a red mud composite filler.
[0086] Comparative Example 2
[0087] The difference between this comparative example and Example 3 is that kaolin is used as the clay material.
[0088] Comparative Example 3
[0089] The difference between this comparative example and Example 3 is that all red mud is replaced by kaolin.
[0090] Comparative Example 4
[0091] This comparative example is different from Example 3 in that the base material does not include tourmaline powder.
[0092] Comparative Example 5
[0093] The difference between this comparative example and Example 3 is that the components of the base material do not include medical stone powder.
[0094] Comparative Example 6
[0095] This comparative example is different from Example 3 in that the base material does not include a foaming agent.
[0096] Comparative Example 7
[0097] The difference between this comparative example and Example 3 is that the components of the base material do not include a carbonaceous combustion aid.
[0098] Comparative Example 8
[0099] The difference between this comparative example and Example 3 is that the components of the inorganic auxiliary materials do not include borax.
[0100] Comparative Example 9
[0101] The difference between this comparative example and Example 3 is that the inorganic auxiliary material does not include quartz sand.
[0102] The simulated sewage was prepared with reference to the water quality indicators of actual domestic sewage. The initial water quality indicators of the simulated sewage were as follows: total phosphorus 4.8 mg / L, ammonia nitrogen 28 mg / L, COD concentration 507 mg / L, turbidity 26 NTU, and pH value 6.87.
[0103] 1. Biofilm test
[0104] The filler was processed into a cube with a side length of 20 mm. Then, the sludge in the aerobic tank of the UCT process of the sewage treatment plant was mixed with simulated sewage at a weight ratio of 1:3 at 25°C, added to the reactor, and immersed in the filler at a filling rate of 9.3 g / L. Then, at a filling rate of 5.0 kgCOD / (m 3 ·d) of organic load continuously enters water, and after the reactor is continuously operated for 24h, the suspended sludge is discharged, and the operation is continued, and the sewage index is continuously monitored, and the COD removal rate and the ammonia nitrogen removal rate are calculated. When the COD removal rate exceeds 55%, and the ammonia nitrogen removal rate exceeds 60%, it is considered that the biofilm is successfully formed, and the time corresponding to the successful biofilm formation of the fillers of each embodiment and comparative example is recorded, which is recorded as the biofilm formation time. Taking the biofilm formation time of comparative example 1 as a benchmark, the ratio between the biofilm formation time of each embodiment and comparative example and the biofilm formation time of comparative example 1 is calculated, and the ratio is recorded as the relative biofilm formation time. The results are shown in Table 2.
[0105] 2. Static adsorption test
[0106] Fillers were added to the simulated sewage at a filling rate of 9.3 g / L, and magnetic stirring was performed at a rate of 160 r / min at 25°C. After 24 hours, the simulated sewage was sampled, and the samples were centrifuged at 6000 r / min for 6 minutes. Then, the ammonia nitrogen concentration and total phosphorus concentration in the supernatant were detected, and the saturated adsorption capacity of each filler for ammonia nitrogen and total phosphorus was calculated. Based on the saturated adsorption capacity of Comparative Example 1, the ratio between the saturated adsorption capacity of ammonia nitrogen in each embodiment and comparative example and the saturated adsorption capacity of ammonia nitrogen in Comparative Example 1 was calculated, and the ratio was recorded as the relative adsorption capacity of ammonia nitrogen. The results are shown in Table 2; based on the saturated adsorption capacity of total phosphorus in Comparative Example 1, the ratio between the saturated adsorption capacity of total phosphorus in each embodiment and comparative example and the saturated adsorption capacity of total phosphorus in Comparative Example 1 was calculated, and the ratio was recorded as the relative adsorption capacity of total phosphorus. The results are shown in Table 2.
[0107] 3. Mechanical properties test
[0108] The filler was processed into a cube with a side length of 20 mm, and then the compressive strength was tested using a ZQ-21B-1 high-precision spring tension and compression testing machine. Taking the compressive strength of Comparative Example 1 as a benchmark, the ratio between the compressive strength of the fillers in each embodiment and comparative example and the compressive strength of Comparative Example 1 was calculated, and the ratio was recorded as the relative compressive strength. The results are shown in Table 2.
[0109] Table 2 Test results
[0110]
[0111] Combining Examples 1-5 and Comparative Example 1 with Table 2, it can be seen that the relative biofilm time measured in Examples 1-5 is shorter, and the relative adsorption of ammonia nitrogen and total phosphorus is higher, indicating that the filler of the present application has a more ideal pore structure, which is not only conducive to the proliferation of microorganisms and biofilm, but also has a relatively good adsorption effect on pollutants. At the same time, the fillers of Examples 1-5 also have higher compressive strength, indicating that the fillers of the present application have achieved improvements in mechanical properties while optimizing the pore structure.
[0112] Combining Example 3 and Comparative Example 2 with Table 2, it can be seen that although Comparative Example 2 has a higher compressive strength, the measured relative biofilm time is longer, and the relative adsorption amounts of ammonia nitrogen and total phosphorus are lower, indicating that when the clay material does not include silt, using only kaolin as the clay material is not sufficient to form a more ideal pore structure, and thus it is difficult to achieve efficient treatment of sewage.
[0113] Combining Example 3 and Comparative Example 3 with Table 2, it can be seen that the compressive strength measured in Comparative Example 3 is lower, the relative biofilm time is longer, and the relative adsorption of ammonia nitrogen and total phosphorus is lower. This is because red mud in the formulation of this application not only directly and indirectly participates in pore formation, but also contributes to mechanical properties. In the absence of red mud, Comparative Example 3 not only fails to fully achieve pore formation, resulting in difficulty in obtaining an ideal pore structure, but also fails to fully improve the mechanical properties of the filler.
[0114] Combining Example 3 and Comparative Example 4 with Table 2, it can be seen that the compressive strength measured in Comparative Example 4 is relatively low, the relative biofilm time is relatively long, and the relative adsorption of ammonia nitrogen and total phosphorus is relatively low. This is because the tourmaline powder promotes gas generation through the iron oxide therein on the one hand, and participates in the formation of the skeleton structure through components such as mullite and aluminum borate produced during the calcination process on the other hand. In the absence of tourmaline powder, Comparative Example 4 not only cannot fully achieve pore formation, resulting in difficulty in obtaining an ideal pore structure, but also fails to fully improve the mechanical properties of the filler.
[0115] In conjunction with Example 3 and Comparative Example 5 and in conjunction with Table 2, it can be seen that the compressive strength recorded by Comparative Example 5 is lower, and the relative biofilm time is longer, and ammonia nitrogen and total phosphorus relative adsorption capacity are lower, this is because the pore structure of medical stone powder itself can participate in the construction of the whole pore structure, and the tridymite in the medical stone powder can be coordinated with components such as mullite and aluminum borate to form a filler skeleton structure. Therefore, in the absence of medical stone powder, Comparative Example 5 not only cannot fully realize pore making, causes being difficult to obtain an ideal pore structure, and the mechanical property of the filler also fails to be fully improved.
[0116] Combining Example 3 and Comparative Example 6 with Table 2, it can be seen that the relative film-forming time measured in Comparative Example 6 is longer, and the relative adsorption amounts of ammonia nitrogen and total phosphorus are lower. This is because in the absence of a pore-forming agent, the total amount of gas generated is reduced, and the interior of the green body cannot generate sufficient expansion pressure to counteract the contraction pressure during the sintering process, making it difficult to obtain a filler with an ideal pore structure.
[0117] Combining Example 3 and Comparative Example 7 with Table 2, it can be seen that the relative film-forming time measured in Comparative Example 7 is longer, and the relative adsorption amounts of ammonia nitrogen and total phosphorus are lower. This is because in the absence of a carbonaceous combustion aid, the total amount of gas generated is reduced, and the sintering cannot be promoted by the heat release of the carbonaceous combustion aid. Therefore, the interior of the green body cannot generate sufficient expansion pressure to counteract the contraction pressure during the sintering process, making it difficult to obtain a filler with an ideal pore structure.
[0118] Combining Example 3 and Comparative Example 8 with Table 2, it can be seen that the relative biofilm time measured in Comparative Example 8 is longer, and the relative adsorption of ammonia nitrogen and total phosphorus is lower. This is because borax can play a fluxing effect together with alkali metal oxides, alkaline earth metal oxides in sludge, and alkali metal minerals such as sodalite in red mud. In the absence of borax, the fluxing effect of Comparative Example 8 is weakened, so the liquid phase generated inside the green body is reduced, and the shrinkage force of the green body cannot be fully reduced, so it is difficult to obtain a filler with an ideal pore structure.
[0119] Combining Example 3 and Comparative Example 9 with Table 2, it can be seen that the relative biofilm-forming time measured in Comparative Example 9 is longer, and the relative adsorption amounts of ammonia nitrogen and total phosphorus are lower. This is because the quartz sand can participate in the formation of the skeleton structure in addition to providing expansion force by converting into tridymite. Therefore, Comparative Example 9 lacking quartz sand cannot generate sufficient expansion pressure to counteract the contraction pressure during the sintering process, so it is difficult to obtain a filler with an ideal pore structure, and the mechanical properties of the filler are also poor.
[0120] Combining Example 3, Example 6 and Table 2, it can be seen that the relative biofilm time measured in Example 6 is shorter, and the relative adsorption amounts of ammonia nitrogen and total phosphorus are higher. This is because magnesium chloride releases the alkaline fluxing components contained in the red mud into the base material in the form of soluble alkali during the aging process, making the distribution of the fluxing components more uniform, thereby reducing the shrinkage force of the green body, optimizing the pore structure of the filler, and improving the treatment efficiency of the filler for sewage.
[0121] It can be seen from Example 6, Example 7-9 and Table 2 that the relative biofilm time measured in Example 7-9 is relatively short, and the relative adsorption of ammonia nitrogen and total phosphorus is relatively high, among which the result of Example 9 is the most ideal, because magnesium oxide can promote the transfer of oxygen during the heating process, so that the combustible components can be burned more fully to produce gas. As the temperature further increases, the decomposition of dolomite itself will also produce carbon dioxide gas, thereby achieving further pore formation. In the later stage of sintering, magnesium oxide (including magnesium oxide produced by the decomposition of dolomite) also promotes the formation of liquid phase as a flux component, reduces the shrinkage pressure of the green body, and finally obtains a filler with a more developed pore structure, improves the contact effect between the filler and the sewage, and improves the treatment efficiency of the filler for sewage.
[0122] Combining Example 9, Example 10 and Table 2, it can be seen that the results measured in Example 9 and Example 10 are close, and there is no significant extension of the film-forming time and a significant decrease in the amount of pollutant adsorption. This is because the magnesium oxide of the present application and the alkaline components such as the soluble sodium dissolved in the red mud can destroy the silicon dioxide film on the surface of silicon carbide, causing the silicon carbide to continue to react, overcoming the obstacles caused by the silicon dioxide film to the oxidation of silicon carbide, thereby fully realizing the foaming of silicon carbide.
[0123] It can be seen from Example 10 and Example 11 and Table 2 that the relative biofilm formation time measured in Example 11 is shorter, and the relative adsorption amounts of ammonia nitrogen and total phosphorus are higher. This is because the silicon carbide fiber has a one-dimensional continuous structure, which can form interconnected pores inside the fiber after oxidation. The synergistic effect of the one-dimensional structure and the interconnected pores promotes the migration of gas inside the filler, thereby optimizing the pore-forming effect and improving the filler's treatment efficiency for sewage.
[0124] It can be seen from Example 11 and Example 12 and Table 2 that the relative biofilm time measured in Example 12 is shorter, and the relative adsorption amounts of ammonia nitrogen and total phosphorus are higher. This is because manganese dioxide can release oxygen during the sintering process and can be used as an oxygen supplier in the oxidation process of silicon carbide, which helps to fully realize the oxidation of silicon carbide, and achieves synergistic pore formation with components such as foaming agent, sludge, red mud, and carbonaceous combustion aid, thereby improving the treatment efficiency of sewage.
[0125] In conjunction with Example 12, Example 13 and in conjunction with Table 2, it can be seen that the relative biofilm time measured in Example 13 is shorter, and the relative adsorption amount of ammonia nitrogen and total phosphorus is higher, this is because hexadecyl trimethylammonium bromide is a cationic surfactant, which can ionize positively charged micelles after being dispersed in an aqueous solution, and electrostatic attraction can occur with negatively charged permanganate ions, thereby improving the dispersion effect of permanganate ions. In the manganese dioxide sol prepared under such conditions, the particle size of the manganese dioxide particles is smaller, and the oxygen supply effect can be more fully achieved, thereby improving the treatment efficiency of sewage.
[0126] Combining Example 13, Example 14 and Table 2, it can be seen that the relative biofilm time measured in Example 14 is shorter, and the relative adsorption amounts of ammonia nitrogen and total phosphorus are higher. This is because manganese dioxide can catalyze the decomposition of hydrogen peroxide to produce oxygen. The oxygen produced in this stage pre-pores the green body, reduces the density of the green body, helps to achieve uniform sintering of the green body, and improves the treatment efficiency of the filler for sewage.
[0127] Combining Example 14, Example 15 and Table 2, it can be seen that the compressive strength measured in Example 15 is significantly higher than that in Example 14. This is because the cordierite phase is produced after sintering the kaolin and magnesium oxide mineral phases, and the cordierite phase can cooperate with the mullite phase produced after calcining tourmaline to strengthen the skeleton structure in the filler. At the same time, under the coordinated cooperation of various components, the filler can still achieve a uniform and sufficient foaming effect, so there is no significant extension of the film-forming time and a significant decrease in the amount of pollutant adsorption.
[0128] Combining Example 15 and Example 16 with Table 2, it can be seen that the compressive strength measured in Example 16 is significantly higher than that in Example 15, and there is no significant extension of the biofilm formation time and a significant decrease in the amount of pollutant adsorption. This is because brown corundum powder can promote the formation of cordierite and has little effect on the pore structure, which can enable the filler to form a relatively ideal pore structure while also having a high mechanical strength.
[0129] The above embodiments are merely explanations of the present application and are not limitations of the present application. After reading this specification, those skilled in the art may make modifications to the embodiments of the present application without any creative contribution as needed. However, as long as they are within the scope of the claims of the present application, they are protected by the patent law.
Claims
1. A method for recycling sludge and red mud to produce porous water treatment fillers, characterized in that: The following steps are involved: (1) The base material is prepared according to the following weight ratio: 25-35% of clay material, 0.3-2% of binder, 20-30% of red mud, 2-10% of tourmaline powder, 4-8% of foaming agent, 6-10% of medical stone powder, 3-5% of carbonaceous combustion aid, and the balance is supplemented to 100% by inorganic auxiliary materials; the tourmaline powder is ferromagnesian tourmaline, the raw material components of the clay material include sludge, the components of the inorganic auxiliary materials include quartz sand, borax, magnesium chloride, and at least one of magnesium oxide and dolomite, and the foaming agent includes silicon carbide powder; in this step, before standing and aging, manganese dioxide sol is added to the base material, and the manganese dioxide sol is prepared according to the following method: A potassium permanganate solution is prepared, and fumaric acid is added to the potassium permanganate solution under stirring, and stirring is continued, and after standing, a manganese dioxide sol is obtained; (2) ball milling the prepared base material, adding water and stirring, and then standing and aging under closed conditions to obtain an aged material; adding the aged material into a mold for pressing and forming to obtain a green body, and standing and setting aside for use; (3) The green body is preheated and then sintered at 1250-1350°C. After cooling, the sintered product is cut and polished to obtain a porous water treatment filler.
2. The method for recycling porous water treatment fillers produced by using sludge and red mud according to claim 1, characterized in that: The foaming agent also includes silicon carbide fibers.
3. The method for recycling porous water treatment fillers produced by using sludge and red mud according to claim 1, characterized in that: In the method for preparing the manganese dioxide sol, hexadecyltrimethylammonium bromide is also added to the potassium permanganate solution before starting stirring.
4. The method for recycling porous water treatment fillers produced by using sludge and red mud according to claim 1, characterized in that: In step (2) of the method, after the green body is obtained, an aqueous hydrogen peroxide solution is sprayed onto the surface of the green body.
5. The method for recycling porous water treatment fillers produced by using sludge and red mud according to claim 1, characterized in that: The clay material also includes kaolin as a component.
6. The method for recycling porous water treatment fillers produced by using sludge and red mud according to claim 5, characterized in that: In step (2) of the method, brown corundum powder is added to the base material before ball milling.
Citation Information
Patent Citations
Multi-scale pore honeycomb ceramic and preparation method thereof
CN111018560A
Lightweight ceramsite for construction muck-based all-solid waste building materials and forming device and preparation method thereof
CN117945785A
Red mud composite filler and preparation method thereof
CN118754298A